Challenges of Teaching Integrated Subjects in the Case of Aesthetics and Physical Education in Some Selected Primary 1st Cycle Schools of Dessie Town - Hailu, Arega Abate (American Scientific Research Journal for Engineering, Technology, and Sciences, 2018)
The purpose of this study was to investigate the major challenges faced during Teaching integrated subjects (Aesthetics and Physical Education) of Dessie town primary first cycle schools. The participants in this study were teachers, and school principals. Among the 44 primary schools found in the Town, 17 (11 government and 6 private) schools were selected by stratified random sampling technique.  From these schools 61 (100%) APE teachers and 8 (47.05%) principals were taken as a sample because their number is manageable. The schools from each strata, principals and class for observation were selected using simple random sampling technique through lottery method. As a method of data gathering tools; questionnaire, interview, observation and document analysis were employed. To analyze the collected data, both quantitative and qualitative methods were used. The results of the study revealed that teaching of integrated subjects (aesthetics and physical education) in the PFCS:  was not at the appropriate standard, because of the following reasons: the inadequate time allotment per week; the inappropriate contents; the absence of sufficient qualified  teachers; the use of APE period for theory than practice; the use of inappropriate instruction and assessment technique for practical physical education, art and music; the facilities and equipment was not sufficiently available or  totally absent; the integration of physical education with art and music; the low attitude of teachers; the inadequate facilities and equipment; the in appropriate contents in the curriculum materials and the low interest of school officials and community for APE were found as a major challenges in teaching Aesthetics and physical education in the PFCS. To overcome these problems the following recommendations have been forwarded. These are: the necessary facilities and equipment should be available; art, music and physical education should be given to students separately; training, workshops and seminars where by the experienced expertise in this area should be adjusted for APE teacher and the curriculum materials specially the selected contents should be revise.